2016
DOI: 10.7603/s40730-016-0008-6
|View full text |Cite|
|
Sign up to set email alerts
|

Quenching of singlet oxygen by natural and synthetic antioxidants and assessment of electronic UV/Visible absorption spectra for alleviating or enhancing the efficacy of photodynamic therapy

Abstract: Abstract-Photodynamic therapy (PDT) is one of the methods involved in cancer treatment exploiting singlet oxygen as a weapon to kill cancer cells. Singlet oxygen, a bizarre reactive oxygen species as it is not related to electron transfer to O 2 but it is one of the most active intermediate involved in biochemical reactions as it directly reacts with all the major macromolecules like DNA, protein, lipids etc, various photosensitized oxidations and in the photodegradation of dyes and polymers. Recent studies ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…However, depending on the concentration of antioxidants, the hormesis effect may promote a pro-oxidative behavior. A recent study showed that several natural and synthetic antioxidants have the potential to enhance the efficacy of PDT, probably due to the quenching action driving the mechanism of PDT towards free radical rather than 1 O 2 [ 184 ]. Anthocyanins are reported as singlet oxygen quenchers.…”
Section: Photodynamic Therapymentioning
confidence: 99%
“…However, depending on the concentration of antioxidants, the hormesis effect may promote a pro-oxidative behavior. A recent study showed that several natural and synthetic antioxidants have the potential to enhance the efficacy of PDT, probably due to the quenching action driving the mechanism of PDT towards free radical rather than 1 O 2 [ 184 ]. Anthocyanins are reported as singlet oxygen quenchers.…”
Section: Photodynamic Therapymentioning
confidence: 99%
“…Some antioxidant molecules are reported to increase the photodamaging effect of photosensitizers used in PDT with many kinds of sensitizers [3].…”
Section: Introductionmentioning
confidence: 99%
“…•− and Imidazole was reported to be a scavenger of singlet oxygen 1 O 2 (Fatima et al 2016). As shown inFig.9, the degradation rate of DCF was 8% with the addition of Imidazole (75mM) and no inhibitory effect was observed when EtOH (2mM), AA(2mM), or TBA (0.05 M) agents were introduced into the reaction system.…”
Section: Reactive Oxygen Species Identi Cation and Activation Mechanismmentioning
confidence: 99%